Environmental, social and governance (ESG) practices in construction supply chain organisations: a comparison of organisational practices and cognitive perceptions of industrial practitioners - Chong, Zhi Loong (2024)
The growing importance of Environmental, Social, and Governance (ESG) practices has led to their adoption across industries as a framework for sustainability, ethical operations, and responsible governance. In Malaysia, the Ministry of Investment, Trade, and Industry's (MITI) i-ESG framework aligns with the nation's development goals. The research gap addresses the limited studies on ESG practices in the Malaysian construction industry. Hence, this research investigates how Malaysian organisations within the construction supply chain leverage ESG practices to mitigate environmental, social, and governance risks while capitalising on potential opportunities. The research approach involves three key steps: (i) tracing the evolution of ESG from its roots in 1960s' Socially Responsible Investing (SRI) to current ESG considerations, (ii) analysing how organisations manage ESG-related practices, and (iii) identifying the cognitive perceptions of ESG practices of industrial practitioners to develop strategies for further improvement of the ESG practices implementations within the Malaysian construction supply chain. Data collection utilises a pilot-tested questionnaire designed to capture organisational ESG practices across the three ESG components. It found a gap between employee understanding of ESG and implemented practices, suggesting potential improvement through greater employee participation. This research analyses the results of a questionnaire that was completed by 211 respondents. Initially, the data underwent descriptive statistical analysis. For the more detailed study, inferential statistical tests such as the Friedman’s Test, KruskalWallis H Test, and Wilcoxon signed-rank Test are employed to enable the drawing of more general conclusions while accounting for potential variations in the characteristics of the respondents. The research contributions highlight how ESG practices can impact the construction industry, governing bodies, and academic and research communities.